Evaluation of in-vitro susceptibility of ß-lactam-resistant Gram-negative bacilli to ceftazidime-avibactam and ceftolozane-tazobactam from clinical samples of a general hospital in southern Brazil - Thaisa Noceti Carvalho; Vanessa Cristine Kobs; Daniela Hille; Roseneide Campos Deglmann; Luiz Henrique Melo; Paulo Henrique Condeixa de França (Revista da Sociedade Brasileira de Medicina Tropical, 2023)
ABSTRACT Background: The spread of carbapenemase- and extended-spectrum β-lactamase (ESBL)-producing gram-negative bacilli (GNB) represent a global public health threat that limits therapeutic options for hospitalized patients. This study aimed to evaluate the in-vitro susceptibility of β-lactam-resistant GNB to ceftazidime-avibactam (C/A) and ceftolozane-tazobactam (C/T), and investigate the molecular determinants of resistance. Methods: Overall, 101 clinical isolates of Enterobacterales and Pseudomonas aeruginosa collected from a general hospital in Brazil were analyzed. Susceptibility to the antimicrobial agents was evaluated using an automated method, and the minimum inhibitory concentrations (MIC50/90) of C/A and C/T were determined using Etest®. The β-lactamase-encoding genes were investigated using polymerase chain reaction. Results: High susceptibility to C/A and C/T was observed among ESBL-producing Enterobacterales (100% and 97.3% for CLSI and 83.8% for BRCAST, respectively) and carbapenem-resistant P. aeruginosa (92.3% and 87.2%, respectively). Carbapenemase-producing Klebsiella pneumoniae exhibited high resistance to C/T (80%- CLSI or 100%- BRCAST) but high susceptibility to C/A (93.4%). All carbapenem-resistant K. pneumoniae isolates were susceptible to C/A, whereas only one isolate was susceptible to C/T. Both antimicrobials were inactive against metallo-β-lactamase-producing K. pneumoniae isolates. Resistance genes were concomitantly identified in 44 (44.9%) isolates, with bla CTX-M and bla SHV being the most common. Conclusions: C/A and C/T were active against microorganisms with β-lactam-resistant phenotypes, except when resistance was mediated by metallo-β-lactamases. Most C/A- and C/T-resistant isolates concomitantly carried two or more β-lactamase-encoding genes (62.5% and 77.4%, respectively).